RELATIONSHIP BETWEEN SELF-EFFICACY AND FEAR OF CANCER RECURRENCE IN CERVIX CANCER PATIENTS - Isran, Isran; Nuraini, Tuti; Afiyanti, Yati; Gayatri, Dewi (Universitas Aisyah Pringsewu, 2024)
Fear of cancer recurrence (FCR) makes cancer patients physically and psychologically disturbed. FCR is caused by cancer patients' lack of ability or competence to exercise self-control (self-efficacy) while undergoing cancer treatment. This study aims to determine the relationship between self-efficacy and fear of recurrence in cervix cancer patients. The method used was cross-sectional, and it was carried out on 169 cervix cancer patients using the CBI (Cancer Behaviour Inventory) instrument to measure self-efficacy and the FCRI (Fear of Cancer Recurrence) instrument to measure fear of recurrence. The results showed that low self-efficacy 90 patients (52,3%) and high fear of cancer recurrence 89 patients (55%). The domain of coping with medication and side effects had the lowest Self-efficacy with 96 patients (56.8%) and the domain of functional impairment was the highest FCR domain with 84 patients (49.7%). However, that a significant relationship between self-efficacy and FCR in cervix cancer patients (p=0,012) with an OR 2,290. Self-efficacy is needed by cancer patients to overcome their fear of cancer recurrence. Therefore, help from health workers is needed to increase the self-efficacy of cancer patients.